2021
DOI: 10.1093/geront/gnab187
|View full text |Cite
|
Sign up to set email alerts
|

Clinimetric Evaluation of the Experienced Communication in Dementia Questionnaire

Abstract: Background and Objectives Tools to measure self-perceived communication between persons with early-stage dementia and their caregivers are lacking. Therefore, we developed a questionnaire for Experienced Communication in Dementia (ECD) with a patient version (ECD-P) and a caregiver version (ECD-C), that contains items on (1) caregiver competence, (2) social communication, (3) communication difficulties, and (4) experienced emotions. This article describes the feasibility and clinimetric evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…This is reversed for ECD-C2. Our clinimetric evaluation of the ECD (Olthof-Nefkens et al, 2021b) showed that the ECD takes about 10 min to complete. The ECD can be filled out independently or with assistance from the researcher if necessary.…”
Section: Quantitative Evaluationmentioning
confidence: 93%
See 1 more Smart Citation
“…This is reversed for ECD-C2. Our clinimetric evaluation of the ECD (Olthof-Nefkens et al, 2021b) showed that the ECD takes about 10 min to complete. The ECD can be filled out independently or with assistance from the researcher if necessary.…”
Section: Quantitative Evaluationmentioning
confidence: 93%
“…We used two questionnaires, which we deemed sufficient for our purpose while being a minimal burden for the participants. The validated ECD was developed in close collaboration with people with dementia and their caregivers (Olthof-Nefkens et al, 2021a), and measures how these persons experience their communication (Olthof-Nefkens et al, 2021b). The ECD is available in two complementary versions: one for the person with dementia (ECD-P) and one for the informal caregiver (ECD-C).…”
Section: Quantitative Evaluationmentioning
confidence: 99%